Framing hope : analyzing NGO communication on Instagram about Middle Eastern refugees - Fintorová, Michaela (2023)
The main goal of this thesis is to provide an overview of NGO communication on Instagram, specifically for Middle Eastern refugees. NGOs use Instagram as a platform for raising awareness, sharing their work, and increasing the reach of their donation campaigns. There has been little profound academic work on how NGOs communicate about Middle Eastern refugees on Instagram. Although it has been almost ten years since the 2015 refugee crisis brought the topic of Middle Eastern refugees to the European context, there is still an influx of MENA refugees even today. The research seeks to identify what aspects NGOs focus on when communicating about refugees. The research is conducted for European NGOs focusing on humanitarian work, working with refugees on the spot or coordinating them from abroad.